Democratic Governance and Educational Development in Nigeria - PhD, Th.D., Moses Baribera GBARAGE (Researchparks Publishing, 2023)
Democratic governance is foundational to sustainable socio-economic development and the safeguarding of human rights. Despite progress in expanding educational access in Nigeria under democratic rule, the quality of education remains a concern. Key factors like curriculum, teaching methods, teacher quality, and the learning environment are pivotal in shaping educational quality. Notwithstanding efforts to revise the curriculum, enhance teacher training, and improve the learning environment, desired outcomes have been elusive. Rising illiteracy rates have contributed to social issues such as terrorism, banditry, kidnapping, militancy, and cultism. Contrary to expectations, education has not brought about the anticipated societal transformation, despite substantial budget allocations. This paradoxical situation, wherein significant investments in education have not translated into social improvements, necessitates closer scrutiny. This study investigates the impact of democratic governance on Nigeria's educational development from 1999 to 2022, using the Human Capital Theory as a lens. Using a qualitative research approach, the study analyzes data from secondary sources such as textbooks, journal publications, internet materials, and government publications. The study reveals a multifaceted impact of democratic governance on Nigeria's education, with key policies enhancing educational access and infrastructure. However, policy implementation has encountered obstacles such as corruption, inadequate funding, poor teacher quality, and socio-cultural factors. Despite the involvement of diverse stakeholders, persistent challenges call for continued collaboration for improved education quality. To strengthen Nigeria's educational development under democratic governance, the study recommends several steps. These include increasing financial commitment to education, aligning it with UNESCO's recommended 15-20% national budget allocation, tackling corruption, improving teacher quality, and enhancing stakeholder engagement. Further, addressing socio-cultural barriers to education through advocacy campaigns and culturally sensitive educational policies is crucial. These measures aim to foster a more inclusive, high-quality educational system in Nigeria.